2015
DOI: 10.1002/etc.3011
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of endocrine biomarkers in juvenile barramundi (Lates calcarifer; Bloch) following exposure to commercial herbicide and surfactant formulations

Abstract: Agricultural pesticides that are known endocrine disrupting chemicals have been detected in waters in the Great Barrier Reef catchment and lagoon. Altered transcription levels of liver vitellogenin (vtg) have been documented in wild populations of 2 Great Barrier Reef fisheries species and were strongly associated with pesticide-containing runoff from sugarcane plantations. The present study examined endocrine and physiological biomarkers in juvenile barramundi (Lates calcarifer) exposed to environmentally rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
1
11
0
1
Order By: Relevance
“…Some studies have shown that DCA may be more toxic than diuron (Giacomazzi and Cochet, 2004;Scheil et al, 2009;Da Rocha et al, 2013); however, studies regarding the toxicity of other metabolites (DCPMU, DCPU) are still limited. A recent study observed that diuron metabolites (mainly DCPMU, DCPU) have antiandrogenic activities in male Nile tilapia (Pereira et al, 2015), although no effect was observed for diuron, which is consistent with another recent study that did not observe estrogenic or antiandrogenic effects of diuron in juvenile barramundi (Lates calcarifer) (Kroon et al, 2015). Additional documented effects of diuron and its metabolites (DCA) in teleosts include morphological (Mhadhbi and Beiras, 2012;Gagnon and Rawson, 2009), biochemical (Sanchez-Muros et al, 2013), physiological (Vinggaard et al, 2000;Miranda et al, 2008;Scheil et al, 2009) and behavioral alterations (Saglio and Trijasse, 1998).…”
Section: Introductionsupporting
confidence: 81%
“…Some studies have shown that DCA may be more toxic than diuron (Giacomazzi and Cochet, 2004;Scheil et al, 2009;Da Rocha et al, 2013); however, studies regarding the toxicity of other metabolites (DCPMU, DCPU) are still limited. A recent study observed that diuron metabolites (mainly DCPMU, DCPU) have antiandrogenic activities in male Nile tilapia (Pereira et al, 2015), although no effect was observed for diuron, which is consistent with another recent study that did not observe estrogenic or antiandrogenic effects of diuron in juvenile barramundi (Lates calcarifer) (Kroon et al, 2015). Additional documented effects of diuron and its metabolites (DCA) in teleosts include morphological (Mhadhbi and Beiras, 2012;Gagnon and Rawson, 2009), biochemical (Sanchez-Muros et al, 2013), physiological (Vinggaard et al, 2000;Miranda et al, 2008;Scheil et al, 2009) and behavioral alterations (Saglio and Trijasse, 1998).…”
Section: Introductionsupporting
confidence: 81%
“…In benthic microalgae, PSII‐inhibiting herbicides reduce growth (Magnusson, Heimann, & Negri, ) and modify diatom community composition (Wood, Mitrovic, Lim, & Kefford, ). In amphibians and fish, atrazine causes osmoregulatory disturbance that affects gill histopathology, gonadal morphology, reproductive fitness, and the dynamics of fish populations (Kroon, Hook, Metcalfe, & Jones, ). The long‐term ecological effects of exposure to herbicides in the GBR region are currently poorly understood.…”
Section: Status and Threats To Wetlands Within The Gbr Catchmentsmentioning
confidence: 99%
“…In other regions, pesticides are thought to be contributing to declining fish populations or to a lack of recovery of fish populations following habitat restoration . To date, very little work has examined the influence of modern‐use pesticides on fish populations in the Great Barrier Reef Catchment Area .…”
Section: Introductionmentioning
confidence: 99%